RETRACTED: Efficacy of Vanadyl Sulfate and Selenium Tetrachloride as Anti-Diabetic Agents against Hyperglycemia and Oxidative Stress Induced by Diabetes Mellitus in Male Rats - Fawziah A. Al-Salmi; Reham Z. Hamza (Current Issues in Molecular Biology)
The use of metals in medicine has grown in popularity in clinical and commercial settings. In this study, the immune-protecting effects and the hypoglycemic and antioxidant activity of vanadyl sulfate (VOSO4) and/or selenium tetrachloride (Se) on oxidative injury, DNA damage, insulin resistance, and hyperglycemia were assessed. Fifty male albino rats were divided into five groups, and all treatments were administrated at 9:00 a.m. daily for 60 successive days: control, STZ (Streptozotocin; 50 mg/kg of STZ was given to 6 h fasted animals in a single dose, followed by confirmation of diabetic state occurrence after 72 h by blood glucose estimation at >280 mg/dl), STZ (Diabetic) plus administration of VOSO4 (15 mg/kg) for 60 days, STZ (Diabetic) plus administration of selenium tetrachloride (0.87 mg/Kg), and STZ plus VOSO4 and, after 1/2 h, administration of selenium tetrachloride at the above doses. The test subjects’ blood glucose, insulin hormone, HbA1C, C-peptide, antioxidant enzymes (superoxide dismutase, catalase, glutathione peroxidase, myeloperoxidase, and xanthine oxidase), markers of lipid peroxidation (MDA), and histological sections of pancreatic tissues were evaluated, and a comet assay was performed. Histological sections in pancreas tissues were treated as indicators of both VOSO4 and selenium tetrachloride efficacy, either alone or combined, for the alleviation of STZ toxicity. The genotoxicity of diabetes mellitus was assessed, and the possible therapeutic roles of VOSO4 or selenium tetrachloride, or both, on antioxidant enzymes were studied. The findings show that the administration of VOSO4 with selenium tetrachloride reduced oxidative stress to normal levels, lowered blood glucose levels, and elevated insulin hormone. Additionally, VOSO4 with selenium tetrachloride had a synergistic effect and significantly decreased pancreatic genotoxicity. The data clearly show that both VOSO4 and selenium tetrachloride inhibit pancreatic and DNA injury and improve the oxidative state in male rats, suggesting that the use of VOSO4 with selenium tetrachloride is a promising synergistic potential ameliorative agent in the diabetic animal model.